Nutritional counseling for lifestyle change - Snetselaar, Linda G. (CRC/Taylor & Francis, 2007)
Offers clinicians with instructions on how to change dietary behavior. This book uses examples from work completed in actual patient settings and emphasizes why a strategy works and what may have happened when it is not successful. It discusses exercise and stress reduction and covers organizational skills necessary to implement lifestyle change